PENERAPAN PAYMENT GATEWAY SEBAGAI JEMBATAN TRANSAKSI YANG AMAN DI ERA DIGITAL. STUDI KASUS PT ABC - Mantik, Hari (Universitas Dirgantara Marsekal Suryadarma, 2024)
E-payment services have been widely used for various purposes, namely: bill payments, ticket orders and others using the ISO 8583 financial standard as a message format. The ISO 8583 standard is used to manage financial transactions consisting of inquiries, payments and reversals. The e-payment system has three entities involved, namely the service provider/biller, payment gateway and financial institution/Collecting Agent (CA). The payment gateway connects the financial transaction process between the CA and the biller, in this process the customer makes a transaction through the CA then the transaction is sent to the payment gateway for further processing and forwarded to the biller, then the biller will provide a response regarding the status of each transaction carried out to the payment gateway and forwarded back to the CA. Tests carried out on this application are to test the functionality of financial transactions on the payment gateway. The existence of this application can help CAs and billers in carrying out financial transactions without having to think about the differences in message formats in the CA and biller systems. The use of the ISO 8583 standard message format is also starting to be emphasized by Bank Indonesia as the regulator in financial transactions.Â Keywords: biller, collecting agent, e-payment, ISO 8583, payment gateway, standardization financial